Foreword: Unravelling threads of time: Intersections of archaeology, myth, and identity - Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2024)
Welcome to the seventh volume of the Ex Novo-Journal of Archaeology, which presents a tapestry woven from diverse scholarly threads, offering insights into the intricate relationships between history, myth, contemporary identity, and activism.